Enhancement of circular RC columns using steel mesh as internal or external confinement under the influence of axial compression loading (Fracture and Structural Integrity, 2021)
Reinforced concrete (RC) columns cannot get supreme confinement by using the customary steel stirrups reinforcement because of the requirements for the spacing distances between the stirrups in addition to concrete continuance trouble. For this, Steel Mesh (SM) externally wrapped around the outer perimeter of the column as contributory confinement are being widely used due to its features. Limited tests focused on using SM for the internal confinement around the reinforcing cage of RC columns. Moreover, no experimental comparison was presented between RC columns internally and externally confined using SM. This paper investigates experimentally the behavior of circular RC columns confined internally or externally by SM. Six short RC columns have been subjected to axial loading until failure. The main studied parameters were SM schemes, number of SM wraps, SM position (internally or externally), and the steel stirrups existence. Results demonstrated that SM could decrease the crack opening, diminish the concrete spalling, increase the maximum failure load, and enhance the ductility, energy absorption, and column stiffness. Furthermore, the partially internal confinement using two wraps of SM around the steel ties presented the maximum capacity with reasonable ductility. In general, internally confined columns showed better behavior than the externally confined one.
Keywords: RC Columns; Steel mesh; Internal confinement; External confinement; Axial loading